FRI0424 Role of IL-10 Gene Polymorphism and C1q Antibodies in Clinicopathological Presentations and Treatment Response in Lupus Nephritis Patients. (10th June 2014) - Tayel, M.; El zawawy, A.; Ibrahim, M.; Waked, E.; El Gendy, S.; Abdel Razek, S.
Abstract : Background: Defining an early and reliable and non invasive biomarker of kidney involvement in SLE is highly desirable. Anti-C1q auto antibodies have been proposed as a useful marker in SLE since their occurrence correlates with renal involvement and, possibly, with nephritic activity. Interleukin-10 (IL-10), is a multifunctional cytokine that plays a crucial role in inflammation and the immune system. High IL-10 expression and the corresponding IL-10 alleles have been suggested to play a causal or exacerbating role in SLE. The promoter of the IL-10 gene is highly polymorphic, IL-10 gene-A/C polymorphism may play a role in the clinical and pathological diversity of lupus nephritis Objectives: evaluate the prevalence of anti-C1q antibodies in patients with SLE, with and without renal involvement, and to correlate it with the activity of the disease. Secondly, to investigate the -592 A/C polymorphism in patients with lupus nephritis and to assess its influence on IL-10 secretion in vivo Methods: 60 SLE patients were recruited in the study, and they were divided into 2 groups, group1, 40 patients with biopsy proven lupus nephritis and group 2, 20 SLE patients without nephritis. Sera were tested for anti-C1q, and IL-10 by enzyme immunoassay. IL-10 gene -592 A/C polymorphism by real time PCR. Frequencies of the genotypes were compared between the two groups Results: Anti-C1q antibodies were found to be significantly higher in patients with active lupus nephritis than those without nephritis with a median of 59.52±56.59 (p=0.001**). In those with active lupus nephritis, anti-C1q was found to correlate significantly with other parameters assessing lupus nephritis activity like C3 (p=0.011*), ESR (p=0.019), anti-dsDNA (p=0.011*), creatinine clearance (p=0.011*), and proteinuria (p=0.006**). No significant differences were found in the distribution of the polymorphism between lupus nephritis and those without nephritis. AC/CC genotypes were more frequent in patients with LN- III and IV than in those with LN class V. There was no significant difference in the serum IL-10 levels in patients with these three genotypes. Conclusions: Anti-C1q antibodies may serve as potential reliable and non invasive marker of SLE disease activity and renal involvement to avoid unnecessary renal biopsies. The IL-10 gene –592 A/C polymorphism appears to be associated and renal pathology of LN, but not associated with serum IL-10 levels. Patients carrying the –592 C allele had a higher risk of proliferative glomerulonephritis, indicating the genetic influence of the IL-10 gene polymorphism in the renal lesions of LN. References: Pickering MC, Botto M, Taylor PR, et al.: systemic lupus erythematosus, complement deficiency, and apoptosis. Adv Immunol 2000;76:227-334. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1060